PENJADWALAN PREVENTIVE MAINTENANCE KOMPONEN KRITIS MESIN BLISTERING LINE 3 DENGAN METODE RELIABILITY CENTERED MAINTENANCE (RCM) II PADA PT. XY - Dyah Ayu Pitaloka, (2022)
PT. XY is a multinational company engaged in the pharmaceutical industry (medicine). The results based on data collection, the highest downtime on line 3 is the Blistering line 3 machine, it shows that the machine is not optimal so it can interfere with the production process. The purpose of this study is to design a schedule for inspection and replacement of critical components on the Blistering line 3 machine by using the RCM II and Age Replacement methods, besides that it also increases the engine improvement after preventive maintenance has been carried out. Based on the results of the highest RPN value, there are 3 critical components, namely embossing, sealing, and simtap. The distribution chosen for the embossing component is the lognormal distribution for TTR and the Weibull distribution for TTF, for the sealing component the lognormal distribution for TTR and the Weibull distribution for TTF, and for the simtap component is the lognormal distribution for TTR and the normal distribution for TTF. The inspection schedule for the embossing component is 35 hours by making 94.1%, the sealing component is 48 hours by making it 99.7% and the simtap component is 55 hours by making it 99.2%. After preventive maintenance of preventive maintenance of age replacement with minimization of downtime, the interval of preventive replacement for embossing components was 105 hours by using 60.17%, sealing components of 166 hours by opening 758%, and simtap components of 133 jams to 79.2 %. Scheduling of inspection and prevention in this study was made for January-June 2022.